Educational Attainment, MRI Changes, and Cognitive Function in Older Postmenopausal Women from the Women's Health Initiative Memory Study. (August 2013) - Rapp, Stephen R.; Espeland, Mark A.; Manson, Joann E.; Resnick, Susan M.; Bryan, Nick R.; Smoller, Sylvia; Coker, Laura H.; Phillips, Lawrence S.; Stefanick, Marcia L.; Sarto, Gloria E.
The relationship between neuropathology and clinically manifested functional and cognitive deficits is complex. Clinical observations of individuals with greater neuropathology who function better than some individuals with less neuropathology are common and puzzling. Educational attainment, a proxy for "cognitive reserve, " may help to explain this apparent contradiction. The objective of this study is to determine if educational attainment is correlated with cognitive decline, brain lesion volume, and total brain atrophy. One thousand three hundred ninety of the 7, 479 community-dwelling women 65 years of age and older enrolled in the Women's Health Initiative Memory Study, two parallel randomized, placebo-controlled clinical trials comparing unopposed and opposed postmenopausal hormone therapy with placebo, were studied. Study participants received annual assessments of global cognitive function with the Modified Mini Mental State exam. One thousand sixty-three participants also received supplemental neurocognitive battery and neuroimaging studies. Magnetic resonance imaging was used to calculate total ischemic lesion and brain volumes. Incident cases of probable dementia and mild cognitive impairment were centrally adjudicated. After adjustment for total lesion and total brain volumes (atrophy), higher educational attainment predicted better cognitive performance ( p < 0.001). Following conversion to dementia/MCI, higher education predicted steeper declines in cognitive function ( p < 0.001). Thus, higher educational attainment was associated with a delay in diagnosis of dementia/MCI in the face of a growing neuropathological load.